2019
DOI: 10.1080/21691401.2019.1601099
|View full text |Cite|
|
Sign up to set email alerts
|

Knocking down miR-384 promotes growth and metastasis of osteosarcoma MG63 cells by targeting SLBP

Abstract: Osteosarcoma is a common malignant bone tumour in adolescents and old people, with highly invasive and metastatic features and poor prognosis. This study aimed to explore the role of miR-384 in osteosarcoma MG63 cells by targeting SLBP. Cell viability, migration and invasion, apoptosis, as well as apoptosis-related factors were evaluated by CCK-8 assay, Transwell assay, flow cytometer and Western blotting, respectively. Dual-luciferase reporter assay was used to determine the target of miR-384. SLBP level was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…miR-486 can promote the cell proliferation and mobility of renal cell carcinoma and inhibit its apoptosis ( 31 ). Several miRNAs have also been identified as effective biomarkers for the prognosis and progression of OS ( 32 , 33 ). miR-1225-5p serves as a tumor suppressor in OS and inhibits the proliferation, migration and invasion of OS cells by targeting Sox9 ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-486 can promote the cell proliferation and mobility of renal cell carcinoma and inhibit its apoptosis ( 31 ). Several miRNAs have also been identified as effective biomarkers for the prognosis and progression of OS ( 32 , 33 ). miR-1225-5p serves as a tumor suppressor in OS and inhibits the proliferation, migration and invasion of OS cells by targeting Sox9 ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-1225-5p serves as a tumor suppressor in OS and inhibits the proliferation, migration and invasion of OS cells by targeting Sox9 ( 32 ). miR-384 is downregulated in OS tissues and cells compared to normal controls and upregulates stem loop binding protein and promotes the growth and metastasis of OS ( 33 ). A previous study reported the downregulation of miR-605 in OS, which indicates that miR-605 may play a role in the progression of OS ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, numerous studies have evaluated the molecular mechanisms of OS. Multiple miRNAs and protein-coding genes have been described and identified as OS biomarkers [2023]. However, the expression profile of miRNA and mRNA in human OS tissues remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…oS demonstrates a high probability to metastasize and damage surrounding tissues, especially within the lung; however, despite the existence of surgical excision and the development of neoadjuvant chemotherapies for patients with oS over the past few decades, the prognosis of oS for 20 year survival remains <20% (3). This poor prognosis is largely due to the anatomical location, tumor size, tumor stage, presence or absence of local recurrence and metastasis, in addition to ineffective chemotherapy regimens (4). Thus, the development of new patient treatment strategies for OS is urgently required.…”
Section: Introductionmentioning
confidence: 99%